SUPER SELECTIVE EMBOLIZATION AND ETOPOSIDE ISOFOSFAMIDE CHEMOTHERAPY ON A PEDIATRIC BLADDER EMBRYONAL RHABDOMYOSARCOMA: A CASE REPORT - Ilmawan, Muhammad; Penta Seputra, Kurnia; Daryanto, Besut (Indonesian Urological Association, 2026)
Objective: This study reports our experience in managing pediatric ERMS cases treated with super-selective embolization and chemotherapy. Case(s) Presentation: We present a case report about a 2-year-old boy with urinary retention. The complaint began with a history of urination difficulty that has not improved with urethral catheter insertion, thus percutaneous cystostomy was performed. However, a mass appeared in the cystostomy wound. Discussion: The biopsy result confirmed the diagnosis as a bladder embryonal rhabdomyosarcoma. Afterward, the patient was treated with super-selective embolization in both of internal iliac artery branches and it succeed to omit the bleeding symptom and growth of the suprapubic mass. The chemotherapy regimen (Etoposide, Mesna, and Ifosfamide) was administered subsequently for 2 cycles and it showed a satisfactory result in form of the reduction of obstruction symptoms and mass volume. Conclusion: Our case report shows that super-selective embolization and Etoposide Isofosfamide chemotherapy can provide adequate local control in a pediatric patient with bladder ERMS. Keywords: Embryonal rhabdomyosarcoma, etoposide, isofosfamide.